Peran Jaksa yang Memiliki Sertifikat Mediator dalam Mekanisme Keadilan Restoratif dalam Sistem Peradilan Pidana - Yunny Nuryanthi (Jurnal Hukum Lex Generalis, 2025)
During the implementation period of law Number 1 of 2023 concerning the Criminal Code (KUHP) and law Number 20 of 2025 concerning the Criminal Procedure of Code (KUHAP), restorative justice as emerged as one form of criminal case resolution that emphasizes the restoration of victim’s conditions, the accountability of offenders into society in order to achieve social harmony. This approach has become an alternative to the conventional criminal justice system in Indonesia. At the Prosecution stage, the Attorney General’s Office of the Republic Indonesia plays important role in implementing restorative justice through the policy of terminating prosecution base on restorative justice. This paper aims to provide a deeper understanding of the concept of restorative justice. This paper aims to provide a deeper understanding of the concepsts of restorative justice, both in terms of its legal basis and its implementation mechanism at the prosecution stage during the transitional period and the simultaneous enforcement of new regulations throughout Indonesia. It is expected that this approach will promote more substantive justice, reduce case backlogs, and encahnce public trust in the criminal justice system in Indonesia, particularly in the Attorney General’s Office of the Republic of Indonesia.